2012
DOI: 10.3354/aei00042
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal extension of wild fish aggregations at Sparus aurata and Thunnus thynnus farms in the north-western Mediterranean

Abstract: Fish farms cause wild fish to aggregate nearby and thus act to modify their distribution, but the spatial and temporal extent of the attraction effect around farms is still poorly understood. We examined attraction using an integrated approach combining 3 factors: spatial extent, depth and season. We analysed an Atlantic bluefin tuna Thunnus thynnus (ABT) and a gilthead seabream Sparus aurata (SB) farm off the north-eastern coast of Spain which represent different fish farming models in the Mediterranean. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 44 publications
2
53
1
Order By: Relevance
“…Additionally, fish abundance and species composition of aggregated fish assemblages around both kinds of fish farms are different (i.e. larger fish aggregation around sea bream/sea bass farms; Bacher et al 2012). This could result in lower invasibility of sea bream/ sea bass farms related to predation rates or competition with pre-existing detritivore species in the fouling community.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fish abundance and species composition of aggregated fish assemblages around both kinds of fish farms are different (i.e. larger fish aggregation around sea bream/sea bass farms; Bacher et al 2012). This could result in lower invasibility of sea bream/ sea bass farms related to predation rates or competition with pre-existing detritivore species in the fouling community.…”
Section: Discussionmentioning
confidence: 99%
“…1). It has been frequently observed that ABT aggregates around tuna farm cages in Croatia and Spain, mainly in spring, summer and autumn season (Šegvić-Bubić et al, 2011;Bacher et al, 2012). Akyol and Ertosluk (2010) recorded ABT at Turkish sea bream and sea bass fish farms.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly recorded families observed aggregated common dolphinfish (Coryphaena hippurus), greater amberjack (Seriola dumerili), Atlantic bonito (Sarda sarda) and chub mackerel (Scomber japonicus), among others (e.g. Sanchez-Jerez et al, 2011;Segvić-Bubić et al, 2011;Bacher et al, 2012Bacher et al, , 2013. Moreover, larger species such as swordfish (Xiphias gladius), which is enlisted in the IUCN Red List of Threatened Species (category: least concern; see http://www.iucnredlist.org), have also been sporadically observed in the vicinity of the farms (Arechavala-Lopez et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assemblages of small wild fish commonly concentrated in large numbers around fish farms, such as members of the Clupeidae, Sparidae, Mugilidae and Carangidae families, also attract larger predatory fin fish species, due to the increase in foraging opportunities. For instance, it is highly frequent to observe aggregated species of both ecological and economic interest such as the common dolphinfish (Coryphaena hippurus), greater amberjack (Seriola dumerili), bluefish (Pomatomus saltatrix), common dentex (Dentex dentex) and Atlantic bluefin tuna (Thunnus thynnus) (SanchezJerez et al, 2011;Šegvić-Bubić et al, 2011;Bacher et al, 2012;. However, swordfish (Xiphias gladius) have never been reported before within the limits of a Mediterranean fish-farm facility.…”
mentioning
confidence: 99%